Facial Reconstruction: A Systematic Review of Current Image Acquisition and Processing Techniques - Sam Tarassoli (Frontiers in Surgery, 2020)
Plastic and reconstructive surgery is based on a culmination of technological advances, diverse techniques, creative adaptations and strategic planning. 3D imaging is a modality that encompasses several of these criteria while encouraging the others. Imaging techniques used in facial imaging come in many different modalities and sub-modalities which is imperative for such a complex area of the body; there is a clear clinical need for hyper-specialized practice. However, with this complexity comes variability and thus there will always be an element of bias in the choices made for imaging techniques.